(untitled) (Globalization and Business, 2018)
The modern conditions of globalization and the expected long-term trends set all the countries of the world in front of special challenges. In addition to it, for all the countries having transitional economy it is very important to manage to develop the strong competitive of the social-economic systems and to transform their countries’ weak aspects (that make the countries’ processes slow down) and to promote to use positive factors in the context of globalization and globalization processes. In the above-mentioned problems the culture (as the factor), the entrepreneurial activities (as the most important resource of the economic growth of the country) and the systemic presentation of the strategic direction of the formation of the economic knowledge of the country take special places. In the paper the main directions of setting the above-mentioned issues and solving these issues are given on Georgia’s example.